The effect of planting date and applications herbicide on the population, weed dry matter and grain yield of chintzy beans - Hajikhani, Samira; Shirani Rad, Amir Hossein; Taheri, Mehdi; Vali Taghaddosi, Mohammad; Saif Zadeh, Saeid (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
In this study the effect of different planting dates and method of combating weed on the population, weed dry matter of yield and chintzy beans were investigated. This study experiment a split block (strip plots) based on a randomized complete block with 4 replications for two years from 2012 Kheirabad research was conducted at the station. The main factor of 4 levels of planting date (a1=10 may, a2=26 may, a3=10 June and a4=26 June) and subplot in 4 levels of herbicide application (b1=Pursuit, b2=Trflan, b3=Hand b4=Weeding weeds and Control) and the sub-subplot Chintzy bean cultivars, two levels of (c1=Talash and c2=COS-16), respectively. During the different stages of sampling at the time of the study, 24 species were identified. It seems that the delay in planting date (late June to early July), reduced weed density and dry the beans. By examining the results of this study concluded that the application of herbicide Pursuit t decreased dry matter and density of weeds beans and the highest yield in the cultivar Talash and planting dates thirds (19 June) and second (4 June months), respectively. In both years, it was observed that the fourth planting date (4 June) due to the cold of early autumn leading to reduced growth period is not suitable for dry bean planting the cultivars. In the end, it is recommended that Cultivar Talash best and most suitable planting dates chintzy beans the perfect weeding grass-weeds, planting dates thirds (10 June) and second (26 May) is. Given the impossibility of complete weeding weeds in beans, chintzy beans, Cultivar best treatment for harvesting the maximum yield in cultivar Talash, application herbicide Pursuit the third planting date (10 June) and second (26 May) is. The results obtained from varieties of Talash can also be fitted in the case of varieties of generalized COS-16 said.